2018
DOI: 10.5530/jcdr.2018.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Association between Myocardial Infarction and Dermatoglyphics: A Cross-Sectional Study

Abstract: Background: Myocardial infarction (MI) is a multifactorial and polygenic cardiovascular disease with high mortality rate. Early diagnosis could help in precautionary measures and change in life style. Many studies used dermatoglyphics as noninvasive technique to predict the incidence of genetic diseases. Here, we tried to assess the association of dermatoglyphic pattern between MI and controls. Methods: We investigated dermatoglyphic patterns among 800 participants (n=400 MI cases and n=400 control groups) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
1
0
2
Order By: Relevance
“…The incidence of loops in both groups male and female, the study found a significantly lesser incidence of loops in MI Patients [10]. Similar findings were observed by Rashad et al, [11] Bhatt et al, [12] and Dhall et al [13]. In contrast, a study done by Shamsadini et al showed different results where the incidence of loops was statistically higher as compared to the control [14].…”
Section: Resultssupporting
confidence: 79%
“…The incidence of loops in both groups male and female, the study found a significantly lesser incidence of loops in MI Patients [10]. Similar findings were observed by Rashad et al, [11] Bhatt et al, [12] and Dhall et al [13]. In contrast, a study done by Shamsadini et al showed different results where the incidence of loops was statistically higher as compared to the control [14].…”
Section: Resultssupporting
confidence: 79%
“…In addition, dermatoglypic patterns are investigated to apply in disease-related risk assessment due to an obvious association between morphological and genetic characteristics [ 7 ]. Therefore, the variability of the finger and palmar ridges properties have been applied as an indicator of evaluating the risk for some multifactorial disorders such as arterial hypertension [ 8 ], cardiovascular diseases [ 9 ], allergy [ 10 ], cancer [ 11 , 12 ] and schizophrenia [ 13 , 14 ]. Many studies have provided evidence that the individual changes on the finger and palmar ridges are associated with multifactorial diseases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Otra de las enfermedades que demuestra asociación con los patrones dermatoglificos es el infarto agudo de miocardio, indicando un aumento estadístico y significativo en la frecuencia de verticilos con un 35,8% acompañado de una disminución en las presillas, destacando que existe diferencias entre poblaciones debido a las características raciales, de igual forma muchos de los casos relacionados al infarto agudo de miocardio (IAM) tienen relación con la presencia de la hipertensión arterial. Se estima que el riesgo relativo para desarrollar un IAM es de un 59% mayor cuando existe la presencia de la hipertensión arterial (Asif et al, 2018). Por el contrario, las patologías respiratorias muestran que los pacientes con asma se relacionan con una disminución en el número de arcos y aumento del número de presillas cubitales (Singh et al, 2016;Hiru & Kumar, 2017).…”
Section: La Dermatoglifia Dactilar Herramienta De Reconocimiento De L...unclassified
“…Estudios realizados en 2018 mostraron que existe una asociación entre la dermatoglifia y los casos de Infarto Agudo de Miocardio, lo que sugiere una contribución para la predicción temprana de la patología en población de la India (Asif, Bhat, Nizamuddin, Mustak, 2018). Se identifica un vacío significativo en Latinoamérica en estudios científicos en relación con la dermatoglifia dactilar y salud Lo expuesto anteriormente, despliega la necesidad de aumentar el trabajo investigativo enfocado a la detección anticipada de las alteraciones metabólicas y cardiovasculares en general, en este caso la hipertensión arterial que permitan afrontar la enfermedad de manera rápida.…”
Section: Introductionunclassified